1992
DOI: 10.1017/s0317167100042517
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous Malformations of the Brain in Children: A Forty Year Experience

Abstract: ABSTRACT:Despite the great capacity for the pediatric brain to recover from stroke, the morbidity and mortality in children who harbor an arteriovenous malformation (AVM) remains high. This study examines the clinical data and management experience with 132 patients with brain AVM from 1949 to 1989. Although the high tendency for a childhood AVM to present with hemorrhage (79%) remained constant for the forty year study period, the associated morbidity and mortality of hemorrhage changed. The mortality rate fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
0
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(87 citation statements)
references
References 30 publications
0
83
0
4
Order By: Relevance
“…The mechanisms of epileptogenesis in AVMs are not fully known, but have been proposed to include cerebral ischemia from neighboring arteriovenous shunting, hemosiderin deposition, gliosis, demyelination, and kindling of excitatory synapses [125, 129, 191, 211, 216]. Various authors have reported the incidence of epilepsy with brain AVMs as anywhere from 12 to 57 % of patients [39, 107, 110, 118, 123, 143]. Epilepsy is more likely in patients with a history of hemorrhage, with larger lesions, and with AVM location in the temporal or frontal lobes [39, 54, 79, 104, 110, 118, 157].…”
Section: Vascular Malformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of epileptogenesis in AVMs are not fully known, but have been proposed to include cerebral ischemia from neighboring arteriovenous shunting, hemosiderin deposition, gliosis, demyelination, and kindling of excitatory synapses [125, 129, 191, 211, 216]. Various authors have reported the incidence of epilepsy with brain AVMs as anywhere from 12 to 57 % of patients [39, 107, 110, 118, 123, 143]. Epilepsy is more likely in patients with a history of hemorrhage, with larger lesions, and with AVM location in the temporal or frontal lobes [39, 54, 79, 104, 110, 118, 157].…”
Section: Vascular Malformationsmentioning
confidence: 99%
“…Several case series have examined rates of seizure outcomes in the surgical treatment of AVMs causing seizures, with Engel class I outcomes reported in 49–94 % of patients [79, 107, 123, 157, 191, 217]. In a recent observational study of 440 patients with supratentorial AVMs undergoing resection at our institution, 130 (30 %) had preoperative seizures [79].…”
Section: Vascular Malformationsmentioning
confidence: 99%
“…Brain AVMs result in 35%–55% of haemorrhagic strokes in children, with an incidence of 1.4 per 100,000 person-years and significant mortalities and morbidities [4, 5]. In one series, mortality reached 25% when averaged over 40 years, with an improvement from 39 to 16% over this time, coinciding with technological advances [6]. The annual bleeding risk of ruptured AVMs in children was reported as 2.71% and increased when associated with aneurysms and deep venous drainage [7].…”
Section: Introductionmentioning
confidence: 99%
“…Brain arteriovenous malformations (bAVM) in children are reported to have a less favourable prognosis than bAVMs in adults, with a mortality rate after hemorrhage above 20 % [17]. Children (< 20 years) with a bAVM were found to present significantly more often with a hemorrhage (56 %) in comparison to adults (43 %), but they were not found to be at an increased risk for a subsequent hemorrhage [8].…”
Section: Introductionmentioning
confidence: 99%